Therapeutic efficacy against Mycobacterium tuberculosis using ID93 and liposomal adjuvant formulations - Baldwin, Susan L.; Reese, Valerie A.; Larsen, Sasha E.; Pecor, Tiffany; Brown, Bryan P.; Granger, Brian; Podell, Brendan K.; Fox, Christopher B.; Reed, Steven G.; Coler, Rhea N. (Frontiers in Microbiology, 2022)
Mycobacterium tuberculosis (M.tb) has led to approximately 1.3 million deaths globally in 2020 according to the World Health Organization (WHO). More effective treatments are therefore required to prevent the transmission of M.tb. Although Bacille Calmette–Guérin (BCG), a prophylactic vaccine against M.tb, already exists, other vaccines are being developed that could help boost BCG’s noted incomplete protection. This includes ID93 + GLA-SE, an adjuvanted protein vaccine which is being tested in Phase 2 clinical trials. The aim of this study was to test new lipid-based adjuvant formulations with ID93 in the context of a therapeutic vaccine, which we hypothesize would act as an adjunct to drug treatment and provide better outcomes, such as survival, than drug treatment alone. The recent success of another adjuvanted recombinant protein vaccine, M72 + AS01E (GlaxoSmithKline Biologicals), which after 3 years provided approximately 50% efficacy against TB pulmonary disease, is paving the way for new and potentially more effective vaccines. We show that based on selected criteria, including survival, T helper 1 cytokine responses, and resident memory T cells in the lung, that a liposomal formulation of GLA with QS-21 (GLA-LSQ) combined with ID93 provided enhanced protection over drug treatment alone.